Efficient composition tuning via cation exchange and improved reproducibility of photovoltaic performance in FAxMA1-xPbI3 planar heterojunction solar cells fabricated by a two-step dynamic spin-coating process. (December 2018) - Jung, Kyungeun; Lee, Jae-Ho; Oh, Kwonwoo; Im, Chan; Do, Junghwan; Kim, Joosun; Chae, Weon-Sik; Lee, Man-Jong
Abstract: We synthesized uniform FA x MA1- x PbI3 perovskite films with a single α phase by a two-step process combined with a dynamically dispensed spin-coating technique. It uses the continuous dropping of precursor solutions with a constant CH3 NH3 I (MAI)/HC(NH2 )2 I (FAI) concentration enabling the kinetically controlled grain growth. Dynamic coating cycles are also changed to facilitate a cation-exchange process, control the degree of the mutual inter-mixing between formamidinium lead triiodide (FAPbI3 ) and methylammonium lead triiodide (MAPbI3 ) and examine the formation process and properties of the mixed perovskite films formed under the excess MA/FA cation environment, which has not been clarified so far. Notably, without additional solvent washing steps, FA x MA1- x PbI3 films are adjustable in composition, pinhole-free, and have various grain sizes depending on the coating cycles. Perovskite solar cells (PSCs) synthesized from FA x MA1- x PbI3 films with two cycles of the dynamic spin coating have achieved a maximum power conversion efficiency (PCE) of 18.50% with an average PCE of 17.06 ± 0.42%, which shows much-improved performance as well as reproducibility compared with 14.79 ± 1.82% obtained from the conventional static spin-coating method. In addition, we first found mixed FA x MA1- x PbI3 perovskites synthesized under an excess cation environment containing local stoichiometric inhomogeneities as well as excess residual cations (C˭N and NH3 + ) acting as recombination traps, which is supported by the calculation of trap densities. Graphical abstract: Highlights: Design a new two-step process combining dynamically dispensed spin-coating technique. Single α phase FA x MA1- x PbI3 are achieved without any solvent washing steps. Depending on dynamic coating cycles, x can be adjusted by an active cation exchange. Maximum 18.50% with an average of 17.06 ± 0.42% shows an excellent reproducibility Perovskites formed under excess cations resulted in the adsorption of excess residual cations acting as traps, which were probed by 2D FTIR imaging.